2017
DOI: 10.1002/ece3.3486
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the benefits of multiple mating on female fertility in wild stalk‐eyed flies

Abstract: Polyandry, female mating with multiple males, is widespread across many taxa and almost ubiquitous in insects. This conflicts with the traditional idea that females are constrained by their comparatively large investment in each offspring, and so should only need to mate once or a few times. Females may need to mate multiply to gain sufficient sperm supplies to maintain their fertility, especially in species in which male promiscuity results in division of their ejaculate among many females. Here, we take a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 98 publications
(196 reference statements)
1
7
0
Order By: Relevance
“…After eclosion, flies of each cross were collected and frozen at −20°C. All males were measured for eyespan (the distance between the outermost tips of the eyes, Chapman et al, 2017;David et al, 1998) and thorax (the distance between the centre of the most posterior point of the head to the joint between the meta-thoracic legs and the thorax, Meade et al, 2017;Rogers, Denniff, Chapman, Fowler, & Pomiankowski, 2008) to a tolerance of 0.01 mm, using a video camera mounted on a monocular microscope and imagej image capture software v.1.46 (Schneider, Rasband, & Eliceiri, 2012). The repeatability of these morphological trait measurements is very high at >99% (David et al, 1998).…”
Section: Adult Morphologymentioning
confidence: 99%
“…After eclosion, flies of each cross were collected and frozen at −20°C. All males were measured for eyespan (the distance between the outermost tips of the eyes, Chapman et al, 2017;David et al, 1998) and thorax (the distance between the centre of the most posterior point of the head to the joint between the meta-thoracic legs and the thorax, Meade et al, 2017;Rogers, Denniff, Chapman, Fowler, & Pomiankowski, 2008) to a tolerance of 0.01 mm, using a video camera mounted on a monocular microscope and imagej image capture software v.1.46 (Schneider, Rasband, & Eliceiri, 2012). The repeatability of these morphological trait measurements is very high at >99% (David et al, 1998).…”
Section: Adult Morphologymentioning
confidence: 99%
“…Moreover, multiple mating is usually costly and risky for females (e.g., time and energy consumption and increased predation and infection; Arnqvist & Rowe, 2005; Harano et al., 2006). Nevertheless, female multiple mating is ubiquitous in many animals (and plants); thus, the evolutionary significance of polyandry has received considerable attention from many evolutionary biologists (e.g., Jennions & Petrie, 2000; Meade et al., 2017; Nason & Kelly, 2020; Pizzari & Wedell, 2013; Simmons, 2005; Yasui, 1998; Zeh & Zeh, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of direct benefits, if females obtain some genetic (indirect) benefits for the offspring (e.g., good genes or genetic diversity) from males, then polyandrous females would be favored (Jennions & Petrie, 2000; Yasui, 1998). These hypotheses have been investigated by numerous empirical and theoretical studies (e.g., Jennions & Petrie, 2000; Meade et al., 2017; Nason & Kelly, 2020; Pizzari & Wedell, 2013; Simmons, 2005; Zeh & Zeh, 2003). Today, the increasing studies have reported the benefits of female multiple mating with different males (e.g., García‐González et al., 2015; Lewis et al., 2020; Power & Holman, 2014; Snook, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that polyandry allows females to gain direct benefits by replenishing sperm and nutrition from the ejaculate (Meade et al 2017), and indirect benefits in terms of offspring genetic diversity and ‘good genes’ (Taylor et al 2014, Rafter et al 2018). However, there are many costs of mating in general, particularly in multiple matings, such as energy costs and disease transmission (Okada et al 2017).…”
mentioning
confidence: 99%